2019
DOI: 10.1021/acsmaterialslett.9b00241
|View full text |Cite
|
Sign up to set email alerts
|

Reductant-Activated, High-Coverage, Covalent Functionalization of 1T′-MoS2

Abstract: Recently developed covalent functionalization chemistry for MoS2 in the 1Tʹ phase enables the formation of covalent chalcogenide-carbon bonds from alkyl halides and aryl diazonium salts. However, the coverage of functional groups using this method has been limited by the negative charge stored in the exfoliated MoS2 sheets to <25-30% per MoS2 unit. We report herein a reductantactivated functionalization wherein one-electron metallocene reductants, such as nickelocene, octamethylnickelocene, and cobaltocene, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 51 publications
(122 reference statements)
5
38
0
Order By: Relevance
“…This concept was recently validated by the Lewis group who showed that the functionalization density of MoS2 by alkyl iodide species could be increased by adding sacrificial reductants to the reaction mixture. 113 This study demonstrated a strong correlation between the strength of the reductant and the coverage of functional groups, supporting our hypothesis that each surface functional group equivalent becomes increasingly difficult to generate and is strongly dependent on the thermodynamic driving force for both generating the radical species and facilitating surface-C bond formation.…”
Section: Covalent Functionalizationsupporting
confidence: 83%
“…This concept was recently validated by the Lewis group who showed that the functionalization density of MoS2 by alkyl iodide species could be increased by adding sacrificial reductants to the reaction mixture. 113 This study demonstrated a strong correlation between the strength of the reductant and the coverage of functional groups, supporting our hypothesis that each surface functional group equivalent becomes increasingly difficult to generate and is strongly dependent on the thermodynamic driving force for both generating the radical species and facilitating surface-C bond formation.…”
Section: Covalent Functionalizationsupporting
confidence: 83%
“…This concept was recently validated by the Lewis group who showed that the functionalization density of MoS2 by alkyl iodide species could be increased by adding sacrificial reductants to the reaction mixture. 112 This study demonstrated a strong correlation between the strength of the reductant and the coverage of functional groups, supporting our hypothesis that each surface functional group equivalent becomes increasingly difficult to generate and is strongly dependent on the thermodynamic driving force for both generating the radical species and facilitating surface-C bond formation.…”
Section: Covalent Functionalizationsupporting
confidence: 83%
“…Interestingly, a similar approach, where alkyl halides were chemically reduced, has recently been used to functionalize 1T'-MoS2. 26 It has been shown earlier that, in the case of diazonium salts, chemical activation via ascorbic acid or iron powder can form aryl radicals for covalent functionalization of a wide range of substrates. [27][28][29] Even before that, this approach was used to perform aryl-aryl coupling in solution, for instance using iodide to induce the reduction of aryl diazonium salts, obtaining quantitative yield of biaryls.…”
Section: Introductionmentioning
confidence: 99%